2015
DOI: 10.12804/apl33.02.2015.03
|View full text |Cite
|
Sign up to set email alerts
|

La producción científica brasileña sobre sentidos y significados del trabajo: una revisión de la utilización terminológica y de las clasificaciones temáticas existentes

Abstract: This paper presents a review of the Brazilian scientific literature on the sense and meaning of work, in order to identify the researchers' use of terminology and the branches of research on the subject. We examine a corpus of 70 papers electronically retrieved from databases for psychology and related fields through software-aided content analysis. The studies on the sense and meaning of work have primarily been developed since the year 2000, especially in the field of psychology. Most of these studies have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 12 publications
0
5
0
6
Order By: Relevance
“…Studies on the topic are, however, incipient. Bendassolli et al (2015), by reviewing the Brazilian scientific literature on the senses and meaning of work, identified that the surveys on the topic were developed especially in the last decade and a half, predominantly in Psychology.…”
Section: Meaningful Workmentioning
confidence: 99%
“…Studies on the topic are, however, incipient. Bendassolli et al (2015), by reviewing the Brazilian scientific literature on the senses and meaning of work, identified that the surveys on the topic were developed especially in the last decade and a half, predominantly in Psychology.…”
Section: Meaningful Workmentioning
confidence: 99%
“…O modelo Meaning of Work (MOW) é reconhecidamente um dos mais influentes nesse campo de investigação. Mas, ainda que a produção científica brasileira sobre os sentidos e significados do trabalho tenha crescido nas últimas décadas, adaptando o MOW ou outros modelos teóricos, os estudos realizados não se voltam à especificidade dos trabalhadores mais velhos (e.g., Bendassolli, Alves, & Torres, 2014;Bendassolli, Coelho-Lima, Pinheiro, & Gê, 2015).…”
Section: Introductionunclassified
“…Desde então, o estudo do MOW (1987) tornou-se um marco na pesquisa científica do sentido do trabalho, de forte influência, principalmente na literatura científica brasileira sobre o tema (BENDASSOLLI et al 2015). Com base nesse modelo, diversos estudos e modelos alternativos do significado do trabalho foram realizados, tais como Soares (1992), Lundberg e Peterson (1994), Bastos, Pinho e Costa (1995), Harpaz e Fu (2002), Pérezgonzález e Vilela (2005) e Morin et al (2007), dentre muitos outros.…”
Section: Resultados E Objetivosunclassified
“…Marcada pela multidisciplinaridade (ARVIDCHVILI E KUCHINKE, 2009, ROSSO, DEKAS E WRZESNIEWSKI, 2010, BENDASSOLLI et al 2015 Quadro 2 -As três dimensões do sentido do trabalho (MOW, 1987) As três dimensões do sentido do trabalho (MOW, 1987)…”
Section: A Pesquisa Do Grupo Mow (1987)unclassified
See 1 more Smart Citation